The Impact of Song Piracy on Digital Platforms on the Income of Indonesian Artists - Iskandar Iskandar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The advancement of digital technology has facilitated music access through various platforms but also presents a significant challenge in the form of song piracy, which greatly impacts the income and career sustainability of Indonesian artists. This study employs a qualitative approach with normative analysis of copyright regulations, music industry reports, and secondary data to identify the impacts and driving factors of piracy and to formulate strategic steps to address it. The findings reveal that song piracy reduces royalties, diminishes the commercial appeal of artists, and is exacerbated by low public awareness, weak law enforcement, and ineffective copyright protection mechanisms on digital platforms. This study recommends synergy between the government, digital platforms, and the public through education, stricter law enforcement, and innovation to create a safer and more sustainable music ecosystem.